Exploration of Long Non-coding RNAs and Circular RNAs in Porcine Milk Exosomes - Zeng, Bin; Chen, Ting; Luo, Junyi; Xie, Meiying; Wei, Limin; Xi, Qianyun; Sun, Jiajie; Zhang, Yongliang (Frontiers in Genetics, 2020)
RNA in milk exosomes can be absorbed in mammalian gastrointestinal tract and function in gene expression regulations. Our previous work demonstrated that porcine milk exosomes (PME) contains large amounts of miRNAs and mRNAs. Increasing evidence suggests that long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) are of particular interest given their key role in diverse biological processes of animals. However, the expression profiles and potential functions of lncRNAs and circRNAs in PME are still unknown. In the present study, we isolated PME by ultracentrifugation and performed a comprehensive analysis of lncRNA and circRNA in PME by using RNA sequencing. As a result, 2,466 novel lncRNAs, 809 annotated lncRNAs and 61 circRNAs were identified in PME. The lncRNAs shared similar characteristics with other mammals in terms of length, exon number and ORFs. However, lncRNAs showed higher level compared with mRNAs. Eight lncRNAs and five circRNAs in PME were selected for PCR identification. Functional enrichment analysis on the target genes of lncRNAs indicated that these genes were involved in cellular macromolecule metabolic, RNA metabolic and immune processes. CircRNAs host genes were enriched in nucleic acid binding and adherence junction. We also evaluated the potential interaction targets between miRNAs and PME lncRNAs or circRNAs, and the results showed that PME lncRNAs and circRNAs have a high density of miRNA target sites. The top 20 highly expressed lncRNAs were found to interact with the proliferation-related miRNAs, and circRNAs potentially targeted many miRNAs that are associated with the intestinal barrier. This study is the first to provide a resource for lncRNAs and circRNAs research of porcine milk. Moreover, the potential interaction between lncRNA/circRNA and miRNA is revealed. The present study expands our knowledge of non-coding RNAs in milk, and additional research is necessary to confirm their exactly physiological functions.